2021
DOI: 10.1002/mds.28645
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Perspective of Dystonia Symptoms during the SARS‐CoV‐2 Pandemic

Abstract: This study was approved by the Ruber International Hospital Ethics Committee. All the data obtained were anonymous. We confirm that we have read the journal's position on issues involved in ethical publication and affirm that this work is consistent with those guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A study on the overall effect of the pandemic on patients with pre‐existing dystonia found that the majority of patients noted worsening of symptoms (65%) [79], approximately one third of patients reported stable symptoms, and <5% noted improvement of dystonia. Forty‐two percent of patients felt that dystonia management had, at some point, been inadequate to their clinical need.…”
Section: Resultsmentioning
confidence: 99%
“…A study on the overall effect of the pandemic on patients with pre‐existing dystonia found that the majority of patients noted worsening of symptoms (65%) [79], approximately one third of patients reported stable symptoms, and <5% noted improvement of dystonia. Forty‐two percent of patients felt that dystonia management had, at some point, been inadequate to their clinical need.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the pandemic has negatively affected individuals living with other movement disorders. Reports describe worsening of motor and non-motor symptoms among those with multiple system atrophy [15] and those with dystonia [16,17]. In a study of individuals with Tourette's syndrome and chronic tic disorders, there was an overall reduction in tic severity but increase in psychiatric symptoms [18].…”
Section: Impact Of the Pandemic On Individuals With Movement Disordersmentioning
confidence: 99%
“…Studies from different countries have demonstrated that individuals with PD experienced worsening motor and nonmotor symptoms during the pandemic [ 8 , 9 , 10 , 11 , 12 , 13 ]. Similarly, the pandemic has negatively affected individuals with other movement disorders such as multiple system atrophy, dystonia, and tic disorders [ 14 , 15 , 16 ]. Overall, telemedicine applied to PD patients increased from 9.7% prior to the pandemic to 63.5% during the pandemic [ 17 ].…”
Section: Changes In Care In Response Due To the Covid-19 Pandemicmentioning
confidence: 99%